DISCOURSE ANALYSIS OF TELEPHONE CONSULTATION: HOW PATIENTS REPORT SYMPTOMS TO DOCTORS FOR NURSING STUDENTS - Irianto, Dhaniel Prasetyo; Nurniati, Emi (KNOWLEDGE: Jurnal Inovasi Hasil Penelitian dan Pengembangan, 2025)
ABSTRACT The transformation of healthcare services due to the COVID-19 pandemic has accelerated the adoption of remote medical consultations, including those over the phone. This practice not only changes the way patients interact with healthcare workers, but also poses new challenges in clinical communication, particularly related to symptom reporting. This article aimed to analyze discursive practices in telephone consultations between patients and doctors, focusing on how patients report symptoms and how doctors respond and clarify them. Using a qualitative approach with a critical discourse analysis method, data were obtained from authentic transcripts of telephone consultations in primary service clinics and analyzed through macro- and micro-discourse structures. The findings suggest that patients tend to use subjective narratives and nonmedical terms to convey symptoms, whereas clinicians control the flow of the conversation through interrupt strategies, closed-ended questions, and repetitive clarification. This pattern reflects an asymmetrical power relationship and opens up space for miscommunication, especially in the absence of nonverbal cues. This study has important implications for nursing education, especially in designing communication training based on remote consultation scenarios that emphasize linguistic sensitivity, empathy, and clarifying abilities. In addition, the integration of discourse analysis in the nursing curriculum can enrich students' understanding of the sociocultural dimensions of medical communication. This article recommends updating communication training policies in educational and healthcare institutions to improve the effectiveness and safety of technology-based medical practices. ABSTRAK Transformasi layanan kesehatan akibat pandemi COVID-19 telah mempercepat adopsi konsultasi medis jarak jauh, termasuk melalui telepon. Praktik ini tidak hanya mengubah cara pasien berinteraksi dengan petugas kesehatan, tetapi juga menimbulkan tantangan baru dalam komunikasi klinis, terutama terkait dengan pelaporan gejala. Artikel ini bertujuan untuk menganalisis praktik diskursif dalam konsultasi telepon antara pasien dan dokter, dengan fokus pada bagaimana pasien melaporkan gejala dan bagaimana dokter menanggapi dan mengklarifikasinya. Dengan menggunakan pendekatan kualitatif dengan metode analisis wacana kritis, data diperoleh dari transkrip otentik konsultasi telepon di klinik layanan primer dan dianalisis melalui struktur wacana makro dan mikro. Temuan menunjukkan bahwa pasien cenderung menggunakan narasi subjektif dan istilah nonmedis untuk menyampaikan gejala, sedangkan dokter mengontrol alur percakapan melalui strategi interupsi, pertanyaan tertutup, dan klarifikasi berulang. Pola ini mencerminkan hubungan kekuatan asimetris dan membuka ruang untuk miskomunikasi, terutama dengan tidak adanya isyarat nonverbal. Penelitian ini memiliki implikasi penting bagi pendidikan keperawatan, terutama dalam merancang pelatihan komunikasi berdasarkan skenario konsultasi jarak jauh yang menekankan kepekaan linguistik, empati, dan kemampuan klarifikasi. Selain itu, integrasi analisis wacana dalam kurikulum keperawatan dapat memperkaya pemahaman mahasiswa tentang dimensi sosial budaya komunikasi medis. Artikel ini merekomendasikan untuk memperbarui kebijakan pelatihan komunikasi di lembaga pendidikan dan kesehatan untuk meningkatkan efektivitas dan keamanan praktik medis berbasis teknologi.